2009
DOI: 10.1093/hmg/ddp383
|View full text |Cite
|
Sign up to set email alerts
|

Stra13 regulates oxidative stress mediated skeletal muscle degeneration

Abstract: Duchenne Muscular Dystrophy (DMD), caused by loss of dystrophin is characterized by progressive muscle cell necrosis. However, the mechanisms leading to muscle degeneration in DMD are poorly understood. Here, we demonstrate that Stra13 protects muscle cells from oxidative damage, and its absence leads to muscle necrosis in response to injury in Stra13-deficient mice. Interestingly, Stra13-/- mutants express elevated levels of TNFalpha, reduced levels of heme-oxygenase-1, and display apparent signs of oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Although Bhlhe40 can regulate the activation of satellite cells by antagonizing Notch signaling and can protect skeletal muscle from oxidative stress-induced damage by activating the expression of HO-1 (25), its function during exercise has not been examined before. The intracellular signals of exercise are transduced by (i) free Ca 2ϩ ions stimulated signaling pathways, (ii) metabolites, (iii) hypoxia, and (iv) mechanical tension (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Bhlhe40 can regulate the activation of satellite cells by antagonizing Notch signaling and can protect skeletal muscle from oxidative stress-induced damage by activating the expression of HO-1 (25), its function during exercise has not been examined before. The intracellular signals of exercise are transduced by (i) free Ca 2ϩ ions stimulated signaling pathways, (ii) metabolites, (iii) hypoxia, and (iv) mechanical tension (39).…”
Section: Discussionmentioning
confidence: 99%
“…Bhlhe40 is ubiquitously expressed in most adult tissues but has especially strong expression in skeletal muscle (22,24), where it regulates the activation of myogenic stem cells named satellite cells by antagonizing Notch signaling (24). Besides, Bhlhe40 can protect skeletal muscle from reactive oxidative species (ROS)-induced damage by activating the expression of a key cytoprotective enzyme, heme oxygenase 1 (HO-1) (25).…”
mentioning
confidence: 99%
“…This is associated with a defect in the size and branching of the differentiated myotubes (23). At the regulatory levels, it was shown that the transcriptional repressor Stra13, which is elevated in dystrophin-deficient mdx mice, protects MuSCs from oxidative damage whereas Stra13 deficiency exacerbates muscular dystrophy (340).…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…Dystrophin-deficient muscles are highly susceptible to the oxidative stress that results from the early onset of muscle degeneration. Muscle necrosis actively occurs following the degeneration, leading to fibrosis and calcification of muscle fibers (Vercherat et al, 2009). It has been suggested that vascular calcification is actively regulated by osteogenic gene expression in vascular smooth muscle cells (Giachelli, 1999).…”
Section: Mechanisms Of Calcificationmentioning
confidence: 99%